(Shelf Life Prediction Of Beef "Dendeng"(Spiced Dried Meat)Using Arrhenius Kinetics) - Rizal Alamsyah; Putiati Mahdar; Muliandi - (Warta Industri Hasil Pertanian, 1995)
This study was aimed at predicting "dendeng" (Spiced dried meat)shelf life employing the application of arrhenius kinetics.It was based on the moisture content increase,the oxygen consumption. And colour changes of dendeng. The experiment were conducted at there temperature levels i.e. 25 degree C,35 degree C,and 45 degree C and Rh 60%.The Factor strongly influenced in predicting shelf life was temperature.The Arrhenius kinetics method based on oxygen consumption showed good result since it gave the short test shelf life.